The effect of task type and perceived demands on postural movements during standing work. (May 2018) - Glinka, Michal; Metzger, Sabrina; Viggiani, Daniel; Callaghan, Jack
Abstract: This study investigated how task demands affect postural behaviour during standing. Twenty-four participants completed three different 12-min tasks: (1) a cognitive task that involved answering questions based on a written passage; (2) a light manual assembly task; and (3) standing quietly with no secondary task. The manual task was associated with the lowest amount of postural movement and a more static pose than the other two conditions. Specifically, postural variability of the lumbar ( F = 5.8; p = 0.01) and thoracic ( F = 4.2; p = 0.03) spine, and fidgets and shifts of the spine ( F = 3.2; p = 0.048), were lowest in the manual task. Additionally, individuals perceiving tasks to be more demanding—regardless of task type—tended to move less ( p = 0.049) than those perceiving lower demands. These findings provide important initial evidence that the type and perceived demands of standing work tasks can affect postural movement. Highlights: Postural movements during standing can mitigate pain. Postural behaviour during standing work is affected by the task we perform. Manual material handling tasks are associated with static standing postures. Tasks cognitive in nature encourage postural movements. When people perceive tasks to demand more effort, they stand more statically.